The Relationship between Body Balance and Futsal Ball Dribbling Skills in State Junior High School 3, South Bengkulu - Jaka Putra; Mesterjon, Mesterjon; Perdima, Feby Elra (Universitas Dehasen Bengkulu, 2025)
Body balance as one of the components of basic motor skills that are very much needed in mastering basic futsal technical skills, especially dribbling. This study aims to determine the relationship between body balance and futsal ball dribbling skills in students who are members of the futsal extracurricular at State Junior High School 3 Bengkulu Selatan. This study uses a quantitative approach with a correlational method. The subjects of the study were 26 students who were members of the futsal extracurricular. Data collection techniques were carried out through body balance tests (holding time in a certain position) and dribbling skills tests (measuring the time to complete dribbling obstacles). The data obtained were analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results of the analysis showed that students' body balance had an average value of 31.86 seconds, with most students in the